An Installation Of The Sensor And Alarm At Ink Pump, When The Ink Starts Thick - Charles Simanullang; Solly Aryza; Parlin Siagian (Jurnal Scientia, 2024)
The use of smart control systems is now very clear and its current use is very broad which is driven by current technological advances. In this paper, we describe the ink protection system on printer machines where d is a means of controlling the ink level where an alarm system is created which is expected in the future. can support the performance needs of printing machines on a large scale. The input given is in the form of an analog quantity and the output produced by the sensor is issued in the form of a Pulse Width Modulation (PWM) quantity which is connected to the printer pump via a pipe to pump ink from the ink tube. Currently, many pump machines have automatic settings to determine the viscosity of the ink liquid. The pump referred to here is a pump that uses air pressure as a power source, especially for printing machines, this pump plays a very important role in pumping ink from outside and into the machine automatically, so in this way the operator on the machine no longer moves ink with the risk that the ink could hit the operator. or worst of all, the ink can spill and damage the printing machine's working system.